LEGAL FRAMEWORK FOR ASSESSING THE EFFECTIVENESS OF HUMANITARIAN DEMINING: LEGAL CONTEXT AND INTERNATIONAL STANDARDS - Botnarenko, Oleksii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The aim of the article is to theoretically substantiate and develop a conceptual system of criteria for assessing the effectiveness of mine action in Ukraine based on international standards, taking into account national regulatory guidelines and practical needs of post-war reconstruction. Research methods: comprehensive, comparative legal and formal legal. Results: the article provides a comprehensive analysis of modern approaches to assessing the effectiveness of mine action, taking into account international standards and national characteristics of Ukraine. The assessment methodology proposed by M.V. Komisarov and M.M. Pidgorodetsky, based on quantitative indicators of risk, safety and rates of territory clearance, is studied, and the possibilities of its partial adaptation for humanitarian demining are considered. The content of the IMAS 14.10 standard is analyzed, which establishes six main criteria for assessing the effectiveness of mine action: feasibility, effectiveness, efficiency, impact, stability, safety and quality. The features of the assessment criteria in emergency situations are outlined, where the emphasis is shifted to timeliness, coverage and protection of the civilian population. It is shown that international standards emphasize the importance of socio-humanitarian aspects of demining, such as community involvement, gender equality and long-term sustainability of results. Within the framework of the analysis of the Ukrainian regulatory field, the content of the Decree of the President of Ukraine No. 722/2019 on Sustainable Development Goals was studied, and their compliance with international assessment criteria in the field of humanitarian demining was revealed. Based on the results of the study, an author’s system of criteria for assessing the effectiveness of mine action activities was proposed, which integrates technical, legal, organizational, social and educational components. It was substantiated that a comprehensive assessment system should comply with the principles of sustainable development, be oriented towards humanitarian goals and contribute to the formation of effective state policy in the field of security and post-war reconstruction.